Identification of quinazoline based inhibitors of IRAK4 for the treatment of inflammation. Issue 12 (15th June 2017) - Smith, Graham F.; Altman, Michael D.; Andresen, Brian; Baker, James; Brubaker, Jason D.; Chen, Hongmin; Chen, Yiping; Childers, Matthew; Donofrio, Anthony; Ferguson, Heidi; Fischer, Christian; Fischmann, Thierry O.; et al.
Graphical abstract: Abstract: Interleukin-1 receptor associated kinase 4 (IRAK4) has been implicated in IL-1R and TLR based signaling. Therefore selective inhibition of the kinase activity of this protein represents an attractive target for the treatment of inflammatory diseases. Medicinal chemistry optimization of high throughput screening (HTS) hits with the help of structure based drug design led to the identification of orally-bioavailable quinazoline based IRAK4 inhibitors with excellent pharmacokinetic profile and kinase selectivity. These highly selective IRAK4 compounds show activity in vivo via oral dosing in a TLR7 driven model of inflammation.